Microplastics Reduce the Negative Effects of Litter-Derived Plant Secondary Metabolites on Nematodes in Soil - Kim, Shin Woong; Liang, Yun; Lozano, Yudi M.; Rillig, Matthias C. (Frontiers in Environmental Science, 2021)
Microplastics and plant litter are ubiquitous in the soil environment, and both materials can influence soil properties and biota. Plant litter releases secondary metabolites (e.g., phenolic compounds) during the decomposition process, including chemical compounds active in plant defense. Effects of microplastics and plant litter on soil biota have been studied independently but we have limited information about the combined effects of both sources of chemicals. Here, we specifically focused on the interaction between plant litter and microplastics, as well as their potential effects on soil biota (i.e., nematodes). We used soils from a previous experiment that included three different types of microplastic fibers (MFs) and four different types of plant litter, which were incubated in the soil in all combinations of materials. After soil incubation (42 days) in the previous experiment, we here tested for effects on nematodes (Caenorhabditis elegans). Plant litter treatments negatively affected the reproduction of nematodes, but these effects were reduced when the soils were incubated along with MFs. We measured the phenolic concentrations in plant litter extracts in a kinetic experiment and found that phenolic concentrations significantly decreased with some of the MF additions. Our results suggest that microplastics can affect the potential effects of natural chemicals such as plant phenolic compounds. We urge future studies to consider this possibility as a key explanatory process underpinning effects of microplastic in the soil environment.